Precise control of conjugated polymer synthesis from step-growth polymerization to iterative synthesis - Chaoran Xu; Jin Dong; Congze He; Jie Yun; Xiangcheng Pan (Giant, 2023)
Conjugated polymers with excellent optoelectronic properties, easy processability, and flexible physical properties are versatile in various applications. In recent years, the precise synthesis of conjugated polymers has attracted much attention due to the close relationship between structure and property. From the perspective of the polymerization mechanism, the synthetic methods of conjugated polymers can be classified into step-growth polymerization, chain-growth polymerization, and iterative synthesis. From step-growth polymerization to iterative synthesis, polymer synthesis becomes more controllable. In this review, we introduce these three synthetic approaches to prepare conjugated polymers with controllable structures based on transition metal-catalyzed cross-coupling reactions and further reveal the control over chemical structures, including length, regioregularity, sequence, and topology. The precise control over the synthesis of conjugated polymer is of great significance for the synthesis of functional polymer with a specific structure, which paves a way for fabricating high-performance devices.